George Strachan of the Mearns : Sixteenth Century Orientalist. - McInally, Tom (Scottish religious cultures historical perspectives., 2020)
Provides an up-to-date study of the life of George Strachan (1572 - 1635), early 17th century Scottish Humanist scholar, Orientalist and traveller.